Trading card game as reading medium in context of Malaysian folklore / Muhammad Hamdi Esahal - Esahal, Muhammad Hamdi (2014)
Malaysian folklore has many of interesting stories and got lot of benefits and moral values inside to the stories. In order to gain the benefits or knowledge from Malaysian folklore, basically reading is the main medium that has been used to deliver the stories. However, most of our youngsters generation has no interest in reading habit. Because of that, they have no interest at all to read the books about Malaysian folklore and in fact they will not know about our Malaysian folklore stories. Then, the focus of the research is to identify the interest in reading non-education and education books, to know about the perception of our teenagers about Malaysian folklore and to analyze the potential of trading card game (TCG) with the element of Malay's mythological stories. In this research, the case study is among TeG group community at Facebook.com and quantitative research method will be used in order to gain the raw data about the frequency, population and perception of the case study about the issues. About 100 questionnaire will be distributed to several group such as Pokemon Trading Card Game Online (Malaysia), Malaysia Duelist club, Cardfight! Vanguard Players (M.V.P), and U.T.C.C Justice Room (Malaysia). In addition, the qualitative research method also will be used on this research. In order to know about the Malaysian folklore, several books will be used by researcher as reference. In this case, this study is only focus on Hikayat Hang Tuah as the scope and limitation. Furthermore, the two films that the researcher will observe in order to understand the view the feel of the story, scene and characters. The films that researcher use is Hang Tuah directed by Phani Majumdar released on 1956 and Hang Jebat directed by Hussain Haniff released on 1961. Other than that, in order to create a new TCG for Malaysian folklore, the researcher will refer to several books that related with TCG which is the main book is TCG for dummies and Pokemon XY trading card game rules book. This book will help the researcher to know about the background of TCG and even to understand about the concept of game play in TCG.